Interactive NPC for Interactive Learning Media Of Indonesian Traditional Music - Vinza Hedi Satria (Meraki: Journal of Creative Industries, 2024)
In the age of digitalization, society has become increasingly accustomed to the utilization of electronic devices. This phenomenon has also had a discernible impact on the gaming market, with an estimated population of over 1.1 billion gamers across the Asia Pacific region. This figure is anticipated to continue its upward trajectory, particularly in the context of the ongoing pandemic, which has compelled individuals to remain at home and conduct their activities primarily online. Consequently, the adaptation of educational resources to align with this digital era is imperative. Within the scope of this research endeavor, we propose the development of an interactive Non-Playable Character (NPC) capable of responding to inquiries pertaining to indigenous musical instruments. To assess the efficacy of our work, we have implemented two distinct evaluation methodologies. Firstly, we have assessed the accuracy of the proposed NPC. Secondly, we have administered a questionnaire to gauge the degree of satisfaction experienced by users when acquiring educational content through our proposed NPC. The results of our evaluation indicate that interactive NPCs can indeed be employed, albeit with a relatively modest impact on enhancing the educational process.